2021
DOI: 10.13057/biodiv/d220615
|View full text |Cite
|
Sign up to set email alerts
|

Species composition, stand characteristics, aboveground biomass, and carbon stock of mangroves in Panabo Mangrove Park, Philippines

Abstract: Abstract. Alimbon JA, Manseguiao MRS. 2021. Species composition, stand characteristics, aboveground biomass, and carbon stock of mangroves in Panabo Mangrove Park, Philippines. Biodiversitas 22: 3130-3137. Mangrove ecosystems have been recognized for their roles in climate change mitigation through their carbon sequestration capacity. However, information on the ecology and carbon stock of mangroves is limited. Thus, this study assessed the species composition, stand characteristics, aboveground biomass, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The mean for ABG and BGB of A. marina was recorded at 71.00 ± 2.30 and 36.07 ± 0.52 Mg ha -1 , respectively, from Malacca, Malaysia (Azman et al 2021). Biomass measurement is a prerequisite for tcarbon stock estimation and the calculation of CO2 sequestration to the environment (Alimbon et al 2021;Howard et al 2014). Biomass estimation enables the comparison of productivity among forest ecosystems.…”
Section: Biomass Estimation and Carbon Contentmentioning
confidence: 99%
“…The mean for ABG and BGB of A. marina was recorded at 71.00 ± 2.30 and 36.07 ± 0.52 Mg ha -1 , respectively, from Malacca, Malaysia (Azman et al 2021). Biomass measurement is a prerequisite for tcarbon stock estimation and the calculation of CO2 sequestration to the environment (Alimbon et al 2021;Howard et al 2014). Biomass estimation enables the comparison of productivity among forest ecosystems.…”
Section: Biomass Estimation and Carbon Contentmentioning
confidence: 99%
“…It is located in the southeastern portion of the city facing Davao Gulf. This coastal village hosts the Panabo Mangrove Park (7°16'20.579" N, 125°40'50.984" E), a mangrove community that houses several mangrove species, including Aegeciras corniculatum, Avicennia marina, Rhizophora apiculata, Rhizophora mucronata, and Sonneratia alba (Alimbon and Manseguiao 2021). Based on the 2015 Census of Population, Barangay J.P. Laurel had a population of 6,561 individuals (Philippine Statistics Authority, 2015).…”
Section: Study Areamentioning
confidence: 99%
“…In the Philippines, very few studies (i.e., Quevedo et al 2019;Tejada and Cauilan 2019;Ballad and Mangabat 2021) explored the local knowledge and perspectives on mangroves and their utilization. In Davao Gulf, which is found in the southeastern part of the Philippines, studies were primarily focused on the assessment of mangrove species diversity (Jumawan et al 2015;Pototan et al 2017Pototan et al , 2021Cardillo and Novero 2018) and recently included aboveground biomass and carbon stock (Alimbon and Manseguiao 2021). Hence, this study aimed to assess the community knowledge and utilization of mangroves in Panabo Mangrove Park, Panabo City, Davao del Norte, Philippines.…”
Section: Introductionmentioning
confidence: 99%
“…The research results of (Murdiyarso et al 2015;Donato et al 2011;Alimbon and Manseguiao 2021) showed that the carbon stock accumulated in mangrove forests varied depending on the species composition and forest age. For example, the average carbon stock of Rhizophora apiculata in Can Gio Mangrove Biosphere Reserve, Ho Chi Minh City, Vietnam was 97.26 tons of carbon/ha (the range was 58.68-138.65 tons of carbon/ha) (Nam 2011).…”
Section: Introductionmentioning
confidence: 99%